Intercultural Quixote: re-enactments and inclusive reading practices - Cantillana, Loreto; Villalobos, Raquel; Catalán, Juan Pablo (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The study aims to analyze the inclusive practices in Mapuche children and adolescents who recreate Cervantes’ novel from the Mapuche worldview. The participants belong to two intercultural primary schools. In their execution, the students complete a workbook with fragments of Don Quixote by Santos Tornero and worksheets on Mapuche culture. The results show the recreation of the work from a syncretic perspective, where the intercultural component and universal values beyond time and culture are relevant.